CONTENT ANALYSIS OF ENGLISH TEXTBOOK â€œWHEN ENGLISH RINGS A BELLâ€ FOR JUNIOR HIGH SCHOOL GRADE SEVEN - Lisdayanti, Lisdayanti; Lio, Asrun; Kamaluddin, Kamaluddin (Universitas Halu Oleo, 2019)
This research was accomplished to find out whether English textbookÂ â€œWhen Â EnglishÂ Rings AÂ Bellâ€ for Junior High Â School on seventh grade fulfilled each criterion of textbook evaluation criteria. The researcher used qualitative analysis as the research design. The data source was collected from English textbook â€œWhen English Rings A Bellâ€ for Junior High School on seventh grade. The instrument of this study was textbook evaluation criteria. The researcher collected the data by using checklist to evaluate the textbook then analyzing the data shown from the checklist and making some interpretations, and finally Â describingÂ the results from the assessment Â table. Â The result confirmed that English textbook â€œWhen English Rings A Bellâ€ for Junior High School on seventh grade was categorized as inappropriate bookÂ because there were only four of fourteen sub- criteria which were fulfilled, namely the objectives were given in the beginning of the book and each chapter, the topic or materials were suitable with the objectives, there were visual materials relevant with the topic, and the instructions of the exercises were clear and easy to understand in terms of completed by examples, while the rest ten criteria were not fulfilled. It was recommended to the teacher to cover the weaknesses of the book by their teaching style or to find another reference outside this textbook.Â Keywords: Textbook, Evaluation Criteria